EVALUASI KANDUNGAN ZAT--ZAT MAKANAN KIAMBANG (Salvinia molesta) DI WADUK BATU TEGI KECAMATAN AIR NANINGAN KABUPATEN TANGGAMUS - Rahadian Fachrudin; Farida Fathul; Liman . (JURNAL ILMIAH PETERNAKAN TERPADU, 2012)
The objective of this experiment was to measure the potential and evaluate the content of nutrients in plants kiambang (Salvinia molesta). In this experiment, the plant is divided into five sections kiambang the young leaves, old leaves, young roots, old roots and whole plants whose results were analyzed descriptively. The results in Reservoir Batu Tegi Salvinia molesta fresh produce as much as 12,600 tons with production of dry air and dry matter respectively - were as much as 512.82 tonnes and 449.28 tons per year. The results of laboratory studies showed the nutrients content of Salvinia molesta in the young roots contain the highest levels of water and ash, but will the lowest levels of dry matter, crude fiber and TDN. Older leaves contain high levels of dry matter, crude fiber and TDN highest, but the lowest moisture and ash will. Young leaves contain the highest levels of protein and fat, but it will be the lowest content of BETN   Keywords : Kiambang, Salvinia molesta, substances of nutrients